Analisis Kualitas Pelayanan Petugas Check-In Counter Pada Maskapai Citilink PT. Gapura Angkasa Di Bandar Udara Internasional Zainuddin Abdul Madjid Lombok - Putria Prianti; Kifni Yudianto (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
With the increasing number of airlines, competition in passenger growth and retention has become increasingly tight. Citilink, one of the leading airlines, understands the importance of providing the best service to its passengers, especially during the check-in process before flights. This research aims to analyze the quality of service provided by check-in counter staff at Citilink, particularly at PT. Gapura Angkasa at Zainuddin Abdul Madjid International Airport, Lombok.Through qualitative research methods including observation, interviews, and documentation, this study aims to understand the level of satisfaction and identify areas for improvement in the check-in counter service. Findings indicate that Citilink has implemented various strategies to enhance passenger experience, including the use of automated information systems and routine training programs for staff. The services provided adhere to established SOPs, demonstrating the airline's commitment to providing consistent, professional, and standards-compliant service.